2018
DOI: 10.1136/bjophthalmol-2018-311954
|View full text |Cite
|
Sign up to set email alerts
|

Delayed surgical treatment of orbital trapdoor fracture in paediatric patients

Abstract: Long recovery time and a high percentage of persistent diplopia are the main problems of delayed trapdoor fracture in children. A prompt surgery within 48 hours is strongly recommended in patients with muscular entrapment even if an urgent treatment is hard to achieve. So are patients with soft-tissue entrapment and significant motility restriction. In the other patients without such indications, even though some recovery might be possible in the long term, a prompt surgery right after diagnosis is still prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…17,18 It should be noted, however, that while entrapment requires urgent surgery preferably within 48 hours, diplopia due to impingement is not an ophthalmologic emergency and surgery should be deferred until it can be performed by an adept surgeon. 19,20 In this study, we found vision-threatening injuries to account for 11.9% of all ocular injuries that presented to the ED. Of these major injuries, posterior segment findings such as retinal tear or choroidal rupture encompassed a small percentage (1.3%) of all injuries.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…17,18 It should be noted, however, that while entrapment requires urgent surgery preferably within 48 hours, diplopia due to impingement is not an ophthalmologic emergency and surgery should be deferred until it can be performed by an adept surgeon. 19,20 In this study, we found vision-threatening injuries to account for 11.9% of all ocular injuries that presented to the ED. Of these major injuries, posterior segment findings such as retinal tear or choroidal rupture encompassed a small percentage (1.3%) of all injuries.…”
Section: Discussionmentioning
confidence: 65%
“… 17 , 18 It should be noted, however, that while entrapment requires urgent surgery preferably within 48 hours, diplopia due to impingement is not an ophthalmologic emergency and surgery should be deferred until it can be performed by an adept surgeon. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Some children have already been "delayed" when they are referred. 18 We suggest having surgical reduction of inferior tissue entrapment within 10 days, post orbital trapdoor fractures. We believe it would bring out better outcomes on motility and result in less diplopia.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, trapdoor fracture is one of the rare facial fractures requiring emergency surgery [ 28 ]. In instances of extraocular muscle entrapment, it is best to perform surgery within 48 h. Delayed surgical treatment may lead to the longer recovery time and worsen the prognosis [ 29 ].…”
Section: Outcomes and Discussionmentioning
confidence: 99%